Formulation and Evaluation Lozenges of Angkak Powder as supportive therapy candidate for DHF - Nurul Hikma; Andi Arjuna; Radhia Riski; Jainer Pasca Siampa (Jurnal Farmasi dan Ilmu Pengobatan, 2022)
Angkak contains monacolin-K compounds which are identical to lovastatin and B complex vitamins (vitamin B12 and folic acid) are believed to play a role in increasing blood platelet levels in DHF. This study aims to determine the optimum formula of angkak powder lozenges with variations of sucrose-mannitol-aspartame sweetener that meet the physical requirements. In this study lozenges were made in 5 formulas with sucrose-mannitol sweetener (F1 14%; without mannitol, F2 10;4%, F3 7;7%, F4 4;10% and F5 without sucrose;14%), while the concentration The aspartame used in the 5 formulas is 1%. The method used is the wet granulation method with the resulting tablet weight is 1000 mg. The lozenges were tested for physical properties including weight uniformity, size uniformity, catch up, and disintegration time. The results showed that the use of sucrose-mannitol-aspartame sweetener produced lozenges that met the requirements for uniformity of weight, uniformity of size, and disintegration time. So, it can be said that F5 is the optimal formula with an average value of 0.042% and a disintegration time of 20.22 minutes.